Double scope recovery technique to manage procedure‐related trouble during wire trimming with a Loop cutter. Issue 4 (12th March 2021) - Nagatomo, Shuzaburo; Minoda, Yosuke; Ihara, Eikichi
Abstract : Watch a video of this article